Comparative Phylogeography of Birds Across the Tocantins–Araguaia Interfluve Reveals a New Biogeographic Suture in the Amazon Far East - Dornas, Tulio; Dantas, Sidnei Melo; Araújo-Silva, Lucas Eduardo; Morais, Fernando; Aleixo, Alexandre (Frontiers in Ecology and Evolution, 2022)
Few phylogeographic studies have focused on understanding the role of the Tocantins-Araguaia Interfluve (TAI) in the diversification of Amazonian biodiversity. Herein we evaluate the phylogeographic relationships of 14 avian lineages present in the TAI and its two neighboring Amazonian Areas of Endemism: the Xingu (XAE) and Belém (BAE). Four alternative scenarios coupling degree of genetic differentiation and area relationships were tested: 1) populations distributed in TAI, BAE and XAE are not genetically differentiated from each other (assumed as the null hypothesis); 2) populations from TAI are more closely related to those from BAE; 3) populations from TAI are more closely related to those from XAE; and 4) TAI populations represent independent or endemic lineages not present in either the BAE or XAE. Molecular analyses considered Bayesian Inference methods and BIC evolutionary models, haplotype sharing and genetic differentiation estimates. We found three distinct phylogeographic patterns: i) four lineages presented no population structure across XAE, TAI and BAE; ii) six lineages were represented in the TAI with distinct phylogroups replacing each other between XAE and BAE, but with varying degrees of contact and evidence of gene-flow within the TAI; and iii) for four lineages, the Tocantins River acted as a barrier isolating BAE phylogroups from those inhabiting both TAI and XAE. These different patterns demonstrate a heterogeneous response to the barrier effects posed by both the Tocantins and Araguaia rivers on the local fauna. Historical geomorphological and hydromorphological factors, such as the presence and absence of paleochannels and anastomosed channel stretches and variations in sedimentation rates support a dynamic history for the Araguaia-Tocantins floodplains, likely accounting for the observed heteregoneity in species´ specific responses. Finally, the scenario of phylogeographic breaks and population subdivision recovered herein along the Tocantins and Araguaia rivers, associated with the existence of contact zones and the occurrence of gene flow, define the TAI as hitherto unknown biogeographic suture zone, localized in southeasternmost Amazonia.